Interannual variability in ozone removal by a temperate deciduous forest. Issue 1 (12th January 2017) - Clifton, O. E.; Fiore, A. M.; Munger, J. W.; Malyshev, S.; Horowitz, L. W.; Shevliakova, E.; Paulot, F.; Murray, L. T.; Griffin, K. L.
Abstract: The ozone (O3 ) dry depositional sink and its contribution to observed variability in tropospheric O3 are both poorly understood. Distinguishing O3 uptake through plant stomata versus other pathways is relevant for quantifying the O3 influence on carbon and water cycles. We use a decade of O3, carbon, and energy eddy covariance (EC) fluxes at Harvard Forest to investigate interannual variability (IAV) in O3 deposition velocities ( v d, O 3 ). In each month, monthly mean v d, O 3 for the highest year is twice that for the lowest. Two independent stomatal conductance estimates, based on either water vapor EC or gross primary productivity, vary little from year to year relative to canopy conductance. We conclude that nonstomatal deposition controls the substantial observed IAV in summertime v d, O 3 during the 1990s over this deciduous forest. The absence of obvious relationships between meteorology and v d, O 3 implies a need for additional long‐term, high‐quality measurements and further investigation of nonstomatal mechanisms. Key Points: Observed factor of 2 in interannual variability (IAV) of ozone dry deposition velocities, dominated by nonstomatal processes Stomatal conductance estimates from two observation‐driven independent models show similar but weak IAV High‐quality, long‐term measurements needed to identify processes driving IAV in ozone dry deposition